Developing Leadership Potential in Students Using SuÌ„Rah Yasin: A Growth-Mindset Perspective - Fontaine, Ridhwan (International Journal of Economics, Management and Accounting, 2019)
This study attempts to build the Islamic leadership potential of groups of students by getting them to watch videos related to SuÌ„rah Yasin throughout the semester. Based on the work of Argyris, it is argued that developing leaders requires double-loop learning. Delahaye called this questioning â€œparadynamic assumptionsâ€. In this study, internalising the paradynamic assumptions of the Qurâ€™aÌ„n is called Qurâ€™aÌ„nic thinking. To develop Muslim leaders, it is assumed that by studying SuÌ„rah Yasin, one can develop Qurâ€™aÌ„nic thinking. This will lead to a growth-mindset, new assumptions about the knowledge of leadership and a new behaviour. To test this assumption, an action research approach was used with two groups of students at the International Islamic University Malaysia. Participants were asked to watch videos related to SuÌ„rah Yasin throughout the semester. SuÌ„rah Yasin was used because it encapsulates Qurâ€™aÌ„nic thinking. These two experiments seemed successful and the lessons related to the experiments are explored.